2017
DOI: 10.1159/000481687
|View full text |Cite
|
Sign up to set email alerts
|

Initial Presentation of Type 2 Diabetes in Adolescents Predicts Durability of Successful Treatment with Metformin Monotherapy: Insights from the Pediatric Diabetes Consortium T2D Registry

Abstract: Background/Aims: Many adolescents with type 2 diabetes (T2D) have rapid deterioration of glycemic control on metformin monotherapy within 2 years of diagnosis. Methods: Enrollment data from the Pediatric Diabetes Consortium T2D Registry were used to categorize 276 youth with a T2D duration ≥2 years into two groups: (1) participants with HbA1c <7.5% on metformin monotherapy (group 1, n = 75) and (2) participants treated with insulin ± metformin (group 2, n = 201). The characteristics of the groups we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Our findings suggest that patients with HbA1c levels <6.5% (<48 mmol/mol) could be eligible for enrollment in current trials of new drugs for youth with T2D, because superior efficacy of the experimental drug could be demonstrated by preventing the rise in HbA1c levels expected in the majority of well‐controlled patients randomized to the placebo group. Our data also point to the need for future studies of novel approaches to lowering HbA1c levels in very poorly controlled pediatric T2D patients, like supervised administration of long‐acting insulin analogs by school personnel or medically supervised dietary interventions …”
Section: Discussionmentioning
confidence: 81%
“…Our findings suggest that patients with HbA1c levels <6.5% (<48 mmol/mol) could be eligible for enrollment in current trials of new drugs for youth with T2D, because superior efficacy of the experimental drug could be demonstrated by preventing the rise in HbA1c levels expected in the majority of well‐controlled patients randomized to the placebo group. Our data also point to the need for future studies of novel approaches to lowering HbA1c levels in very poorly controlled pediatric T2D patients, like supervised administration of long‐acting insulin analogs by school personnel or medically supervised dietary interventions …”
Section: Discussionmentioning
confidence: 81%
“…Bacha et al [1] analyzed the impact of many variables, including metabolic parameters, ethnicity, weight status, and social background, on the outcome of type 2 diabetes mellitus (T2DM) in a large dataset of adolescents. They reported that adolescents with a milder manifestation, only needing treatment with metformin, had a better outcome (defined by HbA1c levels <7.5% four years after diagnosis) than adolescents with a more severe manifestation with initial insulin treatment.…”
mentioning
confidence: 99%
“…Most importantly, shorter diabetes duration and lower HbA1c at manifestation were associated with a better outcome [1]. One might argue from a statistical point of view that a milder manifestation is more likely to be mild also in the follow-up.…”
mentioning
confidence: 99%
See 2 more Smart Citations